Development of digital therapeutics in Hwa-byung treatment: exploring innovation potential in Korean medicine through practitioner survey - Chan-Young Kwon (Frontiers in Medicine)
IntroductionHwa-byung (HB) is a culture-bound anger syndrome prevalent in Korea. While clinical practice guidelines emphasize mind–body modalities (MBMs) and psychotherapies for HB treatment, their implementation in Korean medicine (KM) remains unexplored. Digital therapeutics (DTx) offers potential solutions for treatment delivery barriers. This study investigated current HB treatment practices among KM doctors and their perceptions on DTx implementation.MethodsA nationwide web-based survey of licensed KMDs (N = 864) was conducted in South Korea (August–September 2024). The survey assessed HB treatment practices, utilization of MBMs and psychotherapies, and attitudes toward DTx. Data were analyzed using descriptive statistics.ResultsMost KMDs utilized conventional KM treatments (acupuncture 95.4%, herbal medicine 94.0%), while MBMs (26.2%) and psychotherapies (21.3%) were underutilized despite their recognized importance. Primary barriers included time constraints (65.8%) and insufficient knowledge (62.9%). Treatment typically required 15.6 ± 60.7 weeks with 21.6 ± 37.4 sessions. While DTx knowledge was limited (mean score 2.3 ± 0.9/5), most KMDs (70.6%) expressed interest in DTx development, with 65.4% willing to implement it in practice. The estimated appropriate cost for HB DTx was 24,441.5 ± 13,566.0 KRW per session.ConclusionThis study reveals a significant gap between guidelines and clinical practice in HB treatment, particularly in implementing MBMs and psychotherapies. The positive attitude toward DTx suggests its potential as a practical solution to bridge this gap by providing accessible, standardized delivery of evidence-based psychological interventions within existing clinical workflows. Future DTx development should focus on addressing identified barriers while maintaining alignment with KM principles.